Responses of the freshwater bivalve Dreissena polymorpha to 2,4,6-trinitrotoluene exposure: A biochemical and histopathological study - Yesipova, N. B.; Khromykh, N. O.; Sharamok, T. S.; Marenkov, O. M.; Drehval, I. V.; Didur, O. O.; Savytsky, A. Y. (Regulatory Mechanisms in Biosystems, 2025)
Military operations and the associated pollution of the Ukrainian river ecosystems affect all aquatic inhabitants. Freshwater b i valves are environmentally important stress-sensitive filter feeders, but their adaptive capacity to explosives is currently poorly understood. The a lien bivalve Dreissena polymorpha (zebra mussel), invaded the Dnieper River basin waters and has served as the model object to reveal the biochemical and histological effects of 2,4,6-trinitrotoluene (TNT) action. During chronic (27 days at 2.5 mg/L) exposure, the weight of the experimental mollusks decreased, while their mortality exceeded the control rate. TNT toxic i ty level of LС 50 for D. polymorpha was calculated by Probit analysis. Histopathological changes in the zebra mussel tissues were examined on the 10th and 27th days and showed the dependence on TNT exposure duration. In the gills, lamellae curvature and elongation, cilia degradation and loss, destruction of lamellar apical tips, and cellular abnormalities, such as epithelial cells dysplasia and karyolysis were detected. The h epatopancreas of the experimental zebra mussels demonstrated partially or completely d e stroyed acini, disruption of basement membrane, destruction of tubules, and digestive cells hypertrophy, hyperplasia, vacuolization, and necrosis. Long-term TNT exposure significantly elevated glutathione-S-transferase activity and malondialdehyde content in the D. polymorpha hepatopancreas and gills, marking oxidative stress and indicating accumulation and/or biodegradation of TNT in the mollusks ’ tissues. The results are discussed regarding the specificity of some identified biomarkers as indicators of TNT action. Overall, the biochemical and histopathological responses reflected the metabolic adaptations of zebra mussels to survive in a TNT-polluted environment. Study results indicated sensitivity of D. polymorpha to 2,4,6-trinitrotoluene, while suggested the mollusk’s potential for bioremediation in freshwater ecosystems contaminated with explosives.